Piezoelectric ceramic materials on transducer technology for energy harvesting: A review - Ogbonna, V. E.; Popoola, A. P. I.; Popoola, O. M. (Frontiers in Energy Research, 2022)
Recently, energy harvesting through the means of piezoelectric transducer technology has increasingly attracted the attention of engineers and scientists in producing/generating electricity for human consumption. However, understanding of piezoelectric materials for application in piezoelectric transducer devices in energy harvesting remains important in today’s energy systems engineering. Thus, the present review study is centered on piezoelectric materials for a better understanding of the properties of different piezoelectric materials (ceramic) when placed under mechanical stress or vibration and electrical field during energy harvesting using transducer devices. With the available literature, lead zirconate titanate materials showed to be the most common piezoelectric material with a high energy-generating performance but possessed more mechanical failure and also compromised in a harsh environment compared to lead-free piezoelectric materials. As such, the authors conclude that lead-free piezoelectric materials, such as zinc oxide and barium titanate, remain the best conducive piezoelectric material over lead zirconate titanate, which basically affects the human environment due to its toxicity. Thus, to widen the use of lead-free piezoelectric materials in energy harvesting, owing to their improved properties and environment-friendly nature, the authors recommend further enhancement of the lead-free piezoelectric material properties via nanodielectric filler incorporations using the spark plasma sintering technique.